Accounting Challenges in Recognition and Measurement of Intangible Assets (gjstudies, 2019)
This research paper investigates the persistent and evolving challenges in the recognition and measurement of intangible assets within contemporary financial reportingframeworks. While traditional accounting standards have struggled to adequately capture the value of intangibles such as intellectual property, brand equity, and data assets,the digital economy has exponentially increased their significance, rendering existingmethodologies increasingly inadequate. This study proposes a novel, hybrid valuationframework that integrates principles from information systems governance, continuousauditing, and machine learning to address these deficiencies. We move beyond conventional cost or market-based approaches by developing a multi-attribute, probabilisticmodel that accounts for an asset’s strategic fit, scalability, defensive value, and networkeffects. Our methodology employs a cross-disciplinary lens, drawing from fraud riskmanagement techniques in banking to assess the reliability of internally-generated intangible valuation inputs, and from clinical AI systems to handle sparse or non-financialdata. The paper formulates and addresses three core research questions: (1) How canaccounting frameworks evolve to recognize intangible assets that are generated organically and lack direct transactional evidence? (2) What measurement techniques canprovide reliable, verifiable, and relevant valuations for assets characterized by high uncertainty and rapid obsolescence? (3) How can audit and governance mechanisms beadapted to ensure the integrity of reported intangible asset values? Through a series ofsimulated case studies involving technology and pharmaceutical firms, we demonstratethat our proposed framework reduces valuation volatility, enhances predictive relevancefor future cash flows, and provides a more robust audit trail compared to existing prescribed methods. The findings contribute original insights by redefining the problemfrom one of mere measurement to one of integrated information system design, wherethe accounting for intangibles is embedded within the firm’s strategic data governanceand continuous assurance processes. This represents a significant departure from standard literature and offers a pathway toward more representative financial statementsin an intangible-intensive economic landscape.